SIGNAL DETECTION WITH UNKNOWN PARAMETERS - Y. A. Sidorkina; V. V. Antipov (Научный вестник МГТУ ГА, 2016)
The likelihood ratio of the pulse signal with unknown time position while detecting and detecting the signal with unknown frequency, are considered. Is shown that an FFT algorithm should be performed while detecting the signal with unknown frequency, the maximum value of all spectral samples should be found and compared to the detection threshold. Upon detection of a pulse signal with unknown time position a fast convolution algorithm should be performed, the maximum value of all the spectral inverse FFT samples should be found and compared to the detection threshold. The effectiveness of this algorithm is determined by the sampling distribution of the maximum values of random variables distributed according to Rayleigh.